Close relationship research in Croatia: Studies on relationship quality and adult attachment - Kamenov, Željka (2011)
A summary of close relationship research in Croatia was presented, focusing on studies of marital and friendship relationship quality and studies of adult attachment to family, friends and love partners.
Projekt MZOS
ENG